Varenicline Targets the Reinforcing-Enhancing Effect of Nicotine on Its Associated Salient Cue During Nicotine Self-administration in the Rat - Garcia-Rivas, Vernon; Fiancette, Jean-François; Cannella, Nazzareno; Carbo-Gas, Maria; Renault, Prisca; Tostain, Jessica; Deroche-Gamonet, Véronique (Frontiers in Behavioral Neuroscience, 2019)
Nicotine is acknowledged as the key addictive compound of tobacco. Varenicline (Champix® or Chantix®), mainly acting as a partial agonist at the α4β2 nicotinic receptor, is an approved smoking cessation pharmacotherapy, although with efficacy limited to a portion of smokers. Smokers differ in the motives that drive their drug seeking and Varenicline might be more efficient in some groups more than others. Studies in rodents revealed that nicotine seeking is strongly supported by complex interactions between nicotine and environmental cues, and notably the ability of nicotine to enhance the reinforcing properties of salient environmental stimuli. It is not yet understood whether the decrease of nicotine seeking by acute Varenicline in rats results from antagonism of the primary reinforcing effects of nicotine, of the reinforcement-enhancing effect of nicotine on cues, or of a combination of both. Thanks to a protocol that allows assessment of the reinforcement-enhancing effect of nicotine on cues during self-administration in rats, we showed that Varenicline targets both nicotine reinforcing effects and reinforcement-enhancing effect of nicotine on cues, but importantly, individual variations in the latter, and not in the former, determined the amplitude of acute Varenicline-induced decrease in seeking. These results suggest that Varenicline might be more beneficial in smokers who are more sensitive to nicotine effects on surrounding stimuli, and less for those who seek nicotine primarily for its primary reinforcing effects.